Respuesta :

Step-by-step explanation:

We are provided with an equation and are required to give reasons on how we got the final answer.

(1.) The equation is -3(2x-3) = 25-8x is given.

(2.) In this step, we have simplified the left hand side of the equation by opening the bracket i.e. -6x+9 = 25-8x

(3.) Here, the terms containing 'x' are brought to the left hand side of the equation and simplified i.e. 2x+9 = 25

(4.) Now, the constant terms of the equation are brought to the right side of the equation and simplified i.e. 2x = 16.

(5.) Lastly, the whole equation is divided by 2 in order to get the value of 'x' i.e. x = 8.